On the gyroscopic stabilization of conservative systems - Sosnitskii, S. P. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We consider conservative systems with gyroscopic forces and prove theorems on stability and instability of equilibrium states for such systems. These theorems can be regarded as a generalization of the Kelvin theorem to nonlinear systems.